Gynecological Problems in Surgical Emergency & Casualty Unit in Al- Jamhoory Teaching Hospital, Mosul, Iraq, 2021 - AI-Sarraf, Ahmed M. N.; Hasan, Hassan A.; AL-Gailani, Ali J. (Scientific Journal of Medical Research, 2023)
Background: Some patients having gynecological problems are admitted to the general emergency department because of the close resemblance with general surgical disease. A surgeon, therefore, must be familiar with the appropriate clinical assessment and management technique of such cases. Objective: To study the problem of patients presenting to the surgical A&E unit with a gynecological problem and evaluate the prevalence of these varieties. Methodology: The current study is a Prospective study in Al-Jumhory Teaching Hospital, Accident and Emergency (A& E) Department. During the duty of the general surgical unit. Starting from 1 January 2020 to 31 January 2021. Clinical assessment and routine laboratory investigations were performed on all the patients. More specific investigations were performed when required. All the patients were resuscitated and operated upon UGA. Further management or postoperative care was done in the gynecological ward. Results: During the study period, 95 patients out of total of 1160 patients admitted to the A&E, we found to have gynecological problems, 8.1%. The most common age group was between 16 to 30, comprising 65% of patients. It was observed that the most common problem was due to a ruptured ovarian cyst (49%) and the least common problem was ovarian tumor (3%). The married patients were (67%). The preoperative diagnosis was correct in (60%) of the patients and misdiagnosis was in the remaining (40%). Ovarian problems (47%) were in the right side, and so in all other fallopian tube problems. Conclusions: The rate of making erroneous diagnoses and maltreatment is high because of the close resemblance of clinical features, the nonavailability of certain diagnostic facilities in the emergency, like a pregnancy test and CT scan.